Study of the reusability and stability of nylon nanofibres as an antibody immobilisation surface - Peraile, Inés; Gil-García, Matilde; González-López, Laura; Dabbagh-Escalante, Nushin A.; Cabria-Ramos, Juan C.; Lorenzo-Lozano, Paloma (Beilstein Journal of Nanotechnology, 2024)
In the case of a biological threat, early, rapid, and specific detection is critical. In addition, ease of handling, use in the field, and low-cost production are important considerations. Immunological devices are able to respond to these needs. In the design of these immunological devices, surface antibody immobilisation is crucial. Nylon nanofibres have been described as a very good option because they allow for an increase in the surface-to-volume ratio, leading to an increase in immunocapture efficiency. In this paper, we want to deepen the study of other key points, such as the reuse and stability of these nanofibres, in order to assess their profitability. On the one hand, the reusability of nanofibres has been studied using different stripping treatments at different pH values on the nylon nanofibres with well-oriented antibodies anchored by protein A/G. Our study shows that stripping with glycine buffer pH 2.5 allows the nanofibres to be reused as long as protein A/G has been previously anchored, leaving both nanofibre and protein A/G unchanged. On the other hand, we investigated the stability of the nylon nanofibres. To achieve this, we analysed any loss of immunocapture ability of well-oriented antibodies anchored both to the nylon nanofibres and to a specialised surface with high protein binding capacity. The nanofibre immunocapture system maintained an unchanged immunocapture ability for a longer time than the specialised planar surface. In conclusion, nylon nanofibres seem to be a very good choice as an antibody immobilisation surface, offering not only higher immunocapture efficiency, but also more cost efficiency as they are reusable and stable.
Keywords: biosensor; biothreat; immunodetection; nanofibre; nylon